The Influence of Social Media Influencer Attributes, Perceived Friendship, Psychological Well-Being on Customer Loyalty on the Instagram Application - Juliano Suwandi; Puji Astuti (Formosa Journal of Sustainable Research, 2023)
Social media is online media that allows users to present themselves or communicate, work together, share and interact with other users. The purpose of this study was to explore the relationship between Social Media Influencer Attributes, Perceived Friendship, and Psychological Well-being on customer loyalty on the Instagram application. This study was designed using a purposive sampling method involving 258 Instagram application users in Jakarta, Bogor, Depok, Tangerang and Bekasi. Data were analyzed using structural equation modeling (SEM). Some of the findings in this study are that Social Media Influencer Attributes have a positive influence on Perceived Friendship. Perceived Friendship has a positive effect on Psychological Well-Being. Social Media Influencer Attributes have a positive effect on Psychological Well-Being. Perceived Friendship has a positive effect on customer loyalty. Social Media Influencer Attributes have a positive effect on customer loyalty. There is no effect of Psychological Well-Being on customer loyalty. The managerial implications of this research for Instagram users and researchers are implementing Social Media Influencer Attributes, developing Perceived Friendship, and increasing customer loyalty and placing customers at the core of social media strategy